Examining University Men's Psychobiological and Behavioral Response-Recovery Profile From a Social-Evaluative Body Image Threat. Issue 2 (April 2020) - Smyth, Aidan P. J.; Gammage, Kimberley L.; Lamarche, Larkin; Muir, Cameron
Negative body image, which often results from social-evaluative body image threats, is common in young men and related to many harmful outcomes. Using social self-preservation theory (SSPT), the present study investigated the psychobiological (i.e., shame and cortisol) and behavioral (e.g., submission) response-recovery profile to a social-evaluative body image threat in university men. Participants ( N = 69; M age = 20.80 years, SD = 1.84) were randomly assigned to a high-threat ( n = 34) or low-threat condition ( n = 35). Men in the high-threat condition reported greater post-threat body shame, had greater post-threat cortisol levels, and exhibited more shame-relevant behaviors than men in the low-threat condition. There were no significant differences between conditions for body shame or cortisol at the final post-threat time point (after resting for 30 min). These findings are consistent with SSPT and suggest that men respond to, and recover from, body image threats relatively efficiently.